2016
DOI: 10.1517/14740338.2016.1130125
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of infantile hemangiomas: therapeutic options in regard to side effects and adverse events – a review of the literature

Abstract: Introduction: While options for treatment strategies for infantile hemangiomas (IH) are numerous, evidence-based information about agents, optimal dosage, adverse effects, treatment modality, pretreatment and treatment strategies remain limited. Areas covered: To evaluate side effects and adverse events of medical treatment in children with infantile hemangioma, a comprehensive review of the literature was performed to provide information for daily practice. In total 254 studies were retrieved from medical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
(60 reference statements)
1
15
0
Order By: Relevance
“…Available studies have shown that oral and topical propranolol, topical timolol gel, nadolol and atenolol are highly effective in the treatment of IH. Propranolol it's the most reported beta-blocker used in the treatment of IH [13,14,15,16]. Various dosage schedules have been described for oral propranolol which ranges from 1 to 3 mg/kg/day divided into 3 doses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Available studies have shown that oral and topical propranolol, topical timolol gel, nadolol and atenolol are highly effective in the treatment of IH. Propranolol it's the most reported beta-blocker used in the treatment of IH [13,14,15,16]. Various dosage schedules have been described for oral propranolol which ranges from 1 to 3 mg/kg/day divided into 3 doses.…”
Section: Discussionmentioning
confidence: 99%
“…The following adverse events were observed in patients using oral propranolol: mental depression manifested by insomnia, hypoglycemia, hypotension, bradycardia, congestive heart failure, bronchospasm and acrocyanosis. Rebound growth of lesion was noticed after discontinuation of therapy with propranolol [16]. However, compared with other treatment modalities propranolol is a relatively low risk medication [15,16] which makes it the preferred treatment for problematic IH, although that metaanalysis results shows complications rate of medium 31% of patients at a mean dosage of 2.12 mg/kg/day [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, the lipophilicity of propranolol facilitates its crossing of the blood‐brain barrier, which may induce central nervous system (CNS)‐related side effects, such as sleep disturbance and agitation. Furthermore, patients have experienced intolerable side effects (including sleep disturbance, agitation, bronchial hyperreactivity, bronchospasm and hypoglycaemia), resulting in discontinued use of propranolol and a high risk of recrudescence . Therefore, the search for an alternative therapy with improved efficacy and safety has recently been initiated.…”
Section: Introductionmentioning
confidence: 99%